Do employees and customers understand their new roles for collaborative value co-creation in technology-driven service settings? - Kim, Jinkyung Jenny; Kim, Seongseop (Sam); Ayalew, Zemenu Amare; Chua, Bee Lia; Han, Heesup; Lee, Jiyoung (Elsevier Ltd, 2025)
The use of innovative technologies in restaurant premises has transformed the roles of service employees and customers. The present research aimed to estimate the level of awareness of the transformed roles of the two key parties, and examine how the role stress caused by changed roles affects psychological empowerment, which in turn contributes to collaborative value co-creation. The consequences of joint value co-creation were also examined by testing the effects on satisfaction and behavioral intention. Data were acquired from 312 employees and 393 customers in technology-dominant restaurants, and analyzed using SPSS 26.0 and AMOS 23.0. The level of awareness of the transformed roles of employees was relatively better than for those of customers. The results showed the double-edged sword effect of role stress in creating psychological empowerment. The study also discovered the importance of collaborative value co-creation in the development of positive behavioral intentions for both employees and customers.